Effect of prone positioning on gas exchange according to lung morphology in patients with acute respiratory distress syndrome - Na Young Kim; Si Mong Yoon; Jimyung Park; Jinwoo Lee; Sang-Min Lee; Hong Yeul Lee (Acute and Critical Care, 2022)
Background There are limited data on the clinical effects of prone positioning according to lung morphology. We aimed to determine whether the gas exchange response to prone positioning differs according to lung morphology. Methods This retrospective study included adult patients with moderate-to-severe acute respiratory distress syndrome (ARDS). The lung morphology of ARDS was assessed by chest computed tomography scan and classified as “diffuse” or “focal.” The primary outcome was change in partial pressure of arterial oxygen to fraction of inspired oxygen (PaO2/FiO2) ratio after the first prone positioning session: first, using the entire cohort, and second, using subgroups of patients with diffuse ARDS matched 2 to 1 with patients with focal ARDS at baseline. Results Ninety-five patients were included (focal ARDS group, 23; diffuse ARDS group, 72). Before prone positioning, the focal ARDS group showed worse oxygenation than the diffuse ARDS group (median PaO2/FiO2 ratio, 79.9 mm Hg [interquartile range (IQR)], 67.7–112.6 vs. 104.0 mm Hg [IQR, 77.6–135.7]; P=0.042). During prone positioning, the focal ARDS group showed a greater improvement in the PaO2/FiO2 ratio than the diffuse ARDS group (median, 55.8 mm Hg [IQR, 11.1–109.2] vs. 42.8 mm Hg [IQR, 11.6–83.2]); however, the difference was not significant (P=0.705). Among the PaO2/FiO2-matched cohort, there was no significant difference in change in PaO2/FiO2 ratio after prone positioning between the groups (P=0.904). Conclusions In patients with moderate-to-severe ARDS, changes in PaO2/FiO2 ratio after prone positioning did not differ according to lung morphology. Therefore, prone positioning can be considered as soon as indicated, regardless of ARDS lung morphology.